PENGEMBANGAN MEDIA PEMBELAJARAN AUDIO VISUAL UNTUK MENINGKATKAN PRESTASI BELAJAR PADA MATA PELAJARAN PAI SISWA KELAS VII DI SMP NEGERI 3 PAGAR ALAM - Effi Agustiawan (UNIB Press, 2021)
The purpose of this study was to: (1) To describe appropriate audio-visual learning media in improving the learning achievement of Islamic education in class VII SMP Negeri 3 Pagaralam. (2) To describe the effectiveness of audio-visual learning media in improving learning achievement. This research uses research and development. The population of the research is the VII grade students of SMP Negeri 3 Pagar Alam while the research sample is class VII.2 as the experimental class and VII.1 as the control class. The data collection techniques used in the study were assessment sheets and student test results. The data analysis used was the mean and t-test. Based on the results of the validation of media experts and material experts, it was concluded that the developed audio-visual media was feasible to improve student achievement in learning Islamic religious education in congregational prayer material. Then, based on the results of limited-scale product trials and large-scale trials, it was found that audio-visual learning media could improve student achievement in Islamic Studies subjects in congregational prayer in class VII SMP Negeri 3 Pagar Alam